The influence of computer-aided polyp detection systems on reaction time for polyp detection and eye gaze - Troya, Joel; Fitting, Daniel; Brand, Markus; Sudarevic, Boban; Kather, Jakob Nikolas; Meining, Alexander; Hann, Alexander (Endoscopy, 2022)
Background Multiple computer-aided systems for polyp detection (CADe) have been introduced into clinical practice, with an unclear effect on examiner behavior. This study aimed to measure the influence of a CADe system on reaction time, mucosa misinterpretation, and changes in visual gaze pattern. Methods Participants with variable levels of colonoscopy experience viewed video sequences (n = 29) while eye movement was tracked. Using a crossover design, videos were presented in two assessments, with and without CADe support. Reaction time for polyp detection and eye-tracking metrics were evaluated.Results 21 participants performed 1218 experiments. CADe was significantly faster in detecting polyps compared with participants (median 1.16 seconds [99 %CI 0.40–3.43] vs. 2.97 seconds [99 %CI 2.53–3.77], respectively). However, the reaction time of participants when using CADe (median 2.90 seconds [99 %CI 2.55–3.38]) was similar to that without CADe. CADe increased misinterpretation of normal mucosa and reduced the eye travel distance.Conclusions Results confirm that CADe systems detect polyps faster than humans. However, use of CADe did not improve human reaction times. It increased misinterpretation of normal mucosa and decreased the eye travel distance. Possible consequences of these findings might be prolonged examination time and deskilling.